Pesan Dakwah dalam Film 99 Cahaya di Langit Eropa (Studi Semiotika terhadap Film Karya Guntur Soeharjanto) - Ach Zulfikar Ali; Nasruddin Nasruddin (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2017)
Movie is one of the most effective tools for da’wah in present time and also in future. Regardless of its drawbacks and advantages, it is the mass media that plays important role in influencing and shaping public opinion. It molds public opinion through its contents.Among the most phenomenal movies is ’99 Cahaya di Langit Eropa’. This movie contains strong messages of da’wah, yet it also has the contrary. This study aims to investigate da’wah messages in this movie, both verbal and non-verbal. Two parts of this movie are analyzed. This study is a qualitative study. It employs Roland Barthes semiotics theory to analyze the denotation, connotation and myth in the movie.Data are collected through documentation and library research. Results show that this movie presents values and messages of da’wah Islam. The messages delivered include aqidah, shariah, and akhlaq. It also conveys messages answering contemporary issues in da’wah such as negative stigma of non-Muslim about hijab and polygamy. On the other hand, the movie also has a non-verbal message that appears contradictory to da’wah messages, camel hump hijabstyle.